The cellular automata inside optical chimera states - Ayyad, Marouane; Coulibaly, Saliya (Chaos, solitons and fractals, 2021)
•Investigate the cellular automata-like behavior in the evolution of optical chimera states.•Classify the elementary cellular automata and optical chimera states, using a clustering method based on three metrics.•Our optical chimera states can inherit the properties of a particular class of cellular automata: the complex class. This class operates at the << edge of chaos >> which is extremely useful for computational purposes. Cellular automata are conceptual discrete dynamical systems useful in the theory of information. The spatiotemporal patterns that they produce are intimately related to computational mechanics in distributed complex systems. Here, we investigate their physical implementation in the framework of chimera states in which coherent and incoherent behavior coexist. Hence, chimera states were subject to quantitative and qualitative analyzes borrowing the same tools used to characterize cellular automata. Our results reveal the existence of cellular automata-type dynamics submerged in the dynamics exhibited by our optical chimera states. Thus, they share a panoply of attributes in terms of computational abilities.